Pengaruh Ukuran Direksi, Kepemilikan Institusional, Ukuran Perusahaan, dan CSR terhadap Kinerja Keuangan BUMN - Feren Feren; Indra Pahala; Tresno Eka Jaya R (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to analyze the influence of board size, institutional ownership, company size, and Corporate Social Responsibility (CSR) on the financial performance of State-Owned Enterprises (SOEs) listed on the Indonesia Stock Exchange for the 2019–2024 period. The research method used panel data with a Random Effects Model (REM). The results show that institutional ownership, company size, and CSR significantly influence financial performance, while board size has no significant effect.